ANALYSIS OF INDOOR AND OUTDOOR READING CORNERS MEDIA ON THE READING INTEREST OF HIDAYATUT THOLIBIN KINDERGARTEN STUDENTS - Rivo Panji Yudha; Nihayaturaochmah (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the effect of reading media on children's reading interest at TK Hidayatut Tholibin This study uses a quantitative approach with a research design called Quasi experiment The research will be conducted at TK Hidayatut Tholibin located in West Java Province The population in this study consists of all students in Group B at TK Hidayatut Tholibin, totaling 47, and the sampling technique used is Random Sampling, specifically selecting random groups B1, B2, and B3, each with 15, 16, and 16 students respectively. After selecting 2 sample classes, those 2 classes were randomized again to determine the class to be taught using conventional media and the class to be taught using reading corner media In this case, the class chosen to be taught with reading corner media is class B2, which consists of 16 students, while the other class, B3, will be taught using the conventional method, also with 16 students In this research, data collection instruments consist of observation sheets Data analysis technique involves using a comparative test called Independent Sample T-Test. The research findings indicate that the average reading interest score of the group using indoor reading corners (85.78) is substantially higher compared to the group using outdoor reading corners (59.06), with an average difference of 26.72 The results of the independent samples t-test show a significance value (2-tailed) of 0.000, which is smaller than the significance level of 0.05 This indicates a significant difference between the group using indoor reading corners and the group using outdoor reading corners